Species Composition of Bryophytes at Different Altitudinal Habitats in Langtang National Park, Bagmati Province, Nepal - Pradhan, Nirmala (Journal of Plant Resources, 2023)
The highland bryophytes of the Langtang National Park have not yet been published, despite the fact that it is an easily accessible high-altitude national park for study and research. This study carried out in different locations in and around this park in August 2010, September 2011 and October 2016, revealed a diversity of 80 species of this plant at various elevated habitats. This plant’s diversity was observed high at 2800 to 3000 m of elevations. The lowest known altitude of this study began at 1500 meters in Syabrubesi and went up to 3900 meters in Kyangjn and 4380 meters at the Gosainkund Lake. Some areas like Kutumsng and Gul Bhanjyang (2100-2500 m), Tarkyghyang and Shermathan (2440-2460 m), Nosim Pati (3650 m), Parbati Kund (2600 m), Golphu Bhanjyang (2150 m) and Panch Pokhari (4000 m) were among the unexplored buffer zones that were also considered in this study.